Concrete performance using locally produced kaolin - Pan, W.F.; Razak, H.A. (2010)
This study presents the effect of incorporating local calcined kaolin on the engineering properties and durability of concrete with water/binder ratios in the range of 0·40-0·60. Blended mixtures with cement replacement of 5, 10, 15 and 20 were designed with a target slump of 150±25 mm. From this investigation, it was found that a 10 replacement level was the optimum level in terms of compressive strength. Beyond 10 replacement levels, the strength was decreased but remained higher than the control mixtures with the exception of water/binder ratio of 0·60. With respect to the durability test, the initial surface absorption at 10 min (ISA-10), the sorptivity and the water absorption were enhanced with higher replacement level regardless of water/binder ratio. A linear equation was developed to determine the superplasticiser dosage for a desired workability based on the obtained results. This investigation has shown that the local kaolin has a potential to be incorporated as blended cement as it improves the durability/permeability and compressive strength in comparison with ordinary Portland cement mixtures.